The identification of the missing maternal genome of the allohexaploid camelina (Camelina sativa) - Mandáková, Terezie; Lysak, Martin A (The Plant journal, 2022)
Hexaploid camelina (Camelina sativa; 2n = 6x = 40) is an important oilseed crop closely related to Arabidopsis. Compared to other polyploid crops, the origin of the three camelina subgenomes has begun to be unveiled only recently. While phylogenomic studies identified the diploid C. hispida (2n = 2x = 14) as the paternal genome of C. sativa, the maternal donor genome remained unknown. Because the chromosomes assigned to a putative maternal genome resembled those of diploid C. neglecta (2n = 12), a tetraploid C. neglecta-like genome (2n = 4x = 26) was hypothesized to be the likely maternal ancestor of the hexaploid crop. Here we report the chromosome-level structure of the predicted tetraploid Camelina genome identified among genotypes previously classified together as C. microcarpa and referred to here as C. intermedia. Detailed cytogenomic analysis of the tetraploid genome revealed high collinearity with two maternally inherited subgenomes of the hexaploid C. sativa. The identification of the missing donor tetraploid genome provides new insights into the reticulate evolutionary history of the Camelina polyploid complex and allows us to postulate a comprehensive evolutionary model for the genus. The herein elucidated origin of the C. sativa genome opens the door for subsequent genome modifications and resynthesis of the allohexaploid camelina genome.
Keywords: hybridization; false flax; tetraploidie; Tetraploidy; Polyploidy; Camelina; genom rostlinný; chromosome rearrangements; Arabidopsis; Genome, Plant; diploidie; genome evolution; Diploidy; Brassicaceae; polyploidie; allopolyploidy